Analisis Strategi Pedagang Pakaian di Pasar Atas Kota Bukittinggi untuk Meningkatkan Pendapatan dalam Perspektif Ekonomi Islam - De Vina Bukra; Rahmi Rahmi (Lembaga Yasin AlSys, 2026)
Although traders’ strategies for increasing income have received attention in various studies, studies that specifically examine the condition of traders in revitalized traditional markets that still experience declining income, particularly from the perspective of Islamic economics, remain limited. This study aims to analyze the strategies of clothing traders in increasing their income at Pasar Atas, Bukittinggi City, and to examine their conformity with Islamic economic principles. This study employed a qualitative approach with a case study design, involving a number of clothing traders selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using the interactive qualitative data analysis model. The results showed that the strategies implemented by the traders included aspects of product, price, place, and promotion. The traders provided product variations, set prices flexibly through bargaining, utilized their business locations, and carried out promotion directly and through social media. However, these strategies were still simple and not yet optimally integrated, so the traders’ income tended to be low and unstable. These findings contribute to the development of marketing mix theory in the context of traditional markets while broadening understanding of the integration of Islamic economic principles in trade practices. This study concludes that more planned and integrated management of marketing strategies is important for increasing traders’ income, so greater utilization of digital technology and the implementation of Islamic economic principles by both traders and market managers are needed. The implications of this study include theoretical contributions to enriching the marketing and Islamic economics literature and practical contributions for traders and local governments, while also opening opportunities for further research on the role of digitalization in improving traders’ business performance.